A Procedure for the Characterization of Monocapillary X-Ray Lenses as Condensers for Full-Field Transmission X-Ray Microscopes - Sun, Xuepeng; Shao, Shangkun; Li, Huiquan; Zhang, Xiaoyun; Yuan, Tianyu; Tao, Fen; Sun, Tianxi (Frontiers in Physics, 2022)
Monocapillary x-ray lenses (MXRL) are mostly used as a condenser in full-field transmission x-ray microscopy (TXM) based on synchrotron radiation or laboratory x-ray tube. The performance of the condenser has a significant impact on the imaging quality of the TXM. In this paper, a procedure for the characterization of the MXRL as a condenser is presented. The procedure mainly includes two parts: optical measurement and x-ray test. Through the analysis of the test results in the characterization procedure, relative high-performance condenser can be screened out from a series of MXRL drawn by electric furnace. This is also fed back to the manufacturing process, and therefore, the technology of manufacturing the condenser can be gradually optimized. Moreover, the method of characterizing the performance of the condenser designed for synchrotron radiation TXM by laboratory x-ray tube is proposed to be used in the procedure, which effectively reduces manufacturing time of the high-performance condenser for synchrotron radiation TXM.